2-(1H-Benzimidazol-2-yl)-N-[(E)-(dimethylamino)methylidene]benzenesulfonamide - Ashraf, Adnan (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(16)H(16)N(4)O(2)S, contains two molecules (A and B) with similar conformations: the benzene rings are oriented at dihedral angles of 80.94 (10)° and 84.54 (10)° with their adjacent 1H-benzimidazole groups. In the crystal, the molecules are connected by N—H⋯N hydrogen bonds, forming separate C(4) chains of both the A and B molecules along [010]. The A and B chains are cross-linked by several C—H⋯O interactions involving the benzene rings and the sulfonyl groups, which lead to R (2) (1)(5) loops in the linkage of the chains.